(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This study comparatively investigated the effects of storage condition and time on the microbiological qualities of some stored yoghurts marketed in the Enugu metropolis. The experiment was factorial (2x6x4) involving a completely randomized design (CRD). A total of 96 samples comprising four samples of yoghurt coded A, B, C and D were sourced from different producers and designated as A – Food Science and Technology lab (FST), B – Aqua Rapha yoghurt, C – Chariot yoghurt and D – A.S yoghurt samples. The samples were stored for a period of seventy days under two storage conditions – refrigerated (50C) and room temperatures (28±20C). All samples were analyzed for microbiological parameters such as total viable count (cfu), coliform (cfu), fungal/yeast (cfu) . Statistical analysis was conducted using two-way ANOVA to determine the mean differences. The results showed that total viable count, coliform count, yeast /fungal counts increased with storage time but the rate of increase was significantly higher(<0.05) in room samples. The room samples contained higher total viable, yeast/fungal and coliform counts than the refrigerated counterpart at all storage time irrespective of sample. Deterioration with storage time in terms of total viable count, coliform count was found to be more in sample A and least in sample C .